What pharmacy practitioners need to know about ethics in scientific publishing - Lejla Zunic; Izet Masic (Wolters Kluwer Medknow Publications, 2014)
Pharmacy practice is an ever-changing science and profession. We are witnessing many advancement of pharmacy technology, drug-related information and applied clinical pharmacy literature, which influence our every day's life. Thus, new knowledge generated by research and clinical experience widen the knowledge; change the understanding of drugs and their application in therapeutics and every days life. Thus, policy makers, pharmacists, clinicians and researchers must evaluate and use the information existing in the literature to implement in their healthcare delivery. This paper is prepared for pharmacy researchers and pharmacy students and analyzes the major principles of ethical conduct in general science and also closely related topics on ghost authorship, conflict of interest, assigning co-authorship, redundant/repetitive and duplicate publication. Furthermore, the paper provides an insight into fabrication and falsification of data, as the most common form of scientific fraud. Scientific misconduct goes against everything that normal scientific method wants to reach for and pharmacy practitioners as one the first line available health care professionals all round the world should be enough aware of its importance and details when they want to evaluate the medical and pharmaceutical literature and deliver unbiased and ethically published knowledge of drugs both for the research or during consultations for patients care.